Patients knowledge about side effects of orthodontic treatment - Amalia, Mia; Anggani, Haru Setyo; Ismaniati, Nia Ayu (Padjadjaran Journal of Dentistry, 2011)
Disharmonious of dental arrangement can possibly create problems for the patient, such as the masticatory function, esthetical, psychosocial, and also the increased risk of trauma and periodontal disease. These are reasons for a patient to seek orthodontic treatment. The aim of this study was to know the patient’s knowledge about the side effects possibility that they receive during orthodontic treatment. The side effects include pain experience during orthodontic treatment, the possibility of soft tissue damage, email demineralization, loss of tooth vitality, periodontal problem, root resorption, temporomandibular joint disorders, and relapse. A cross-sectional study was conducted in patients who registered at Orthodontic Department, Faculty of Dentistry, Universitas Indonesia on March-June 2009. The participants of this study were 100 patients, consist of 86 women and 14 men respectively. Twenty-seven questions about the side-effects of orthodontic treatment were used to obtain the patient’s knowledge and the result was categorized into 3 groups, good, average and poor. The result of the study showed that patient’s knowledge about the side effect of pain experience during orthodontic treatment was average and the patient’s knowledge about the possibility of soft tissue damage due to orthodontic treatment was good. However, the patient’s knowledge about the possibility of email demineralization, loss of tooth vitality, periodontal problem, root resorption, temporomandibular joint disorders and relapse due to orthodontic treatment was low.